The Efficacy of a Health Promotion Intervention for Indigenous Women: Reclaiming Our Spirits - Varcoe, Colleen (Journal of interpersonal violence, 2021)
Indigenous women globally are subjected to high rates of multiple forms of violence, including intimate partner violence (IPV), yet there is often a mismatch between available services and Indigenous women’s needs and there are few evidence-based interventions specifically designed for this group. Building on an IPV-specific intervention (Intervention for Health Enhancement After Leaving [iHEAL]), “Reclaiming Our Spirits” (ROS) is a health promotion intervention developed to address this gap. Offered over 6 to 8 months in a partnership between nurses and Indigenous Elders, nurses worked individually with women focusing on six areas for health promotion and integrated health-related workshops within weekly Circles led by an Indigenous Elder. The efficacy of ROS in improving women’s quality of life and health was examined in a community sample of 152 Indigenous women living in highly marginalizing conditions in two Canadian cities. Participants completed standard self-report measures of primary (quality of life, trauma symptoms) and secondary outcomes (depressive symptoms, social support, mastery, personal agency, interpersonal agency, chronic pain disability) at three points: preintervention (T1), postintervention (T2), and 6 months later (T3). In an intention-to-treat (ITT) analysis, Generalized Estimating Equations (GEE) were used to examine hypothesized changes in outcomes over time. As hypothesized, women’s quality of life and trauma symptoms improved significantly pre- to postintervention and these changes were maintained 6 months later. Similar patterns of improvement were noted for five of six secondary outcomes, although improvements in interpersonal agency were not maintained at T3. Chronic pain disability did not change over time. Within a context of extreme poverty, structural violence, and high levels of trauma and substance use, some women enrolled but were unable to participate. Despite the challenging circumstances in the women’s lives, these findings suggest that this intervention has promise and can be effectively tailored to the specific needs of Indigenous women.